Rubella virus strain-associated differences in the induction of oxidative stress are independent of their interferon activation - Zobel, Sarah; Stanifer, Megan; Boulant, Steeve (Viruses, 2018)
Rubella virus (RV) infection impacts cellular metabolic activity in a complex manner with strain-specific nutritional requirements. Here we addressed whether this differential metabolic influence was associated with differences in oxidative stress induction and subsequently with innate immune response activation. The low passaged clinical isolates of RV examined in this study induced oxidative stress as validated through generation of the reactive oxygen species (ROS) cytoplasmic hydrogen peroxide and mitochondrial superoxide. The addition of the cytoplasmic and mitochondrial ROS scavengers N-acetyl-l-cysteine and MitoTEMPO, respectively, reduced RV-associated cytopathogenicity and caspase activation. While the degree of oxidative stress induction varied among RV clinical isolates, the level of innate immune response and interferon-stimulated gene activation was comparable. The type III IFNs were highly upregulated in all cell culture systems tested. However, only pre-stimulation with IFN β slightly reduced RV replication indicating that RV appears to have evolved the ability to counteract innate immune response mechanisms. Through the data presented, we showed that the ability of RV to induce oxidative stress was independent of its capacity to stimulate and counteract the intrinsic innate immune response.
Gesehen am 03.04.2020